Hadis Kebijakan Pembatasan Wilayah Saat Terjadi Pandemi: Analisis Parsial dan Simultan Riwayat Abdurrahman Bin Auf dalam Shahih Al-Bukhari - Nugroho, Nur Abdul Kholik; Damanhuri, Damanhuri; Ahmadi, Ahmadi (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
Hadith on Regional Restriction Policy During a Pandemic: Partial and Simultaneous Analysis of Abdurrahman Bin Auf's Narration in Sahih Al-Bukhari The purpose of this study is to conduct a partial and simultaneous analysis of the hadith on regional restriction policies during a pandemic. The scope of this research is the main hadith narrated by Abdurrahman bin Auf which was takhrij by Imam Bukhari. Data relating to the hadith and the quality of each narrator was collected using the documentation method. Data analysis using content analysis method. Based on a partial analysis, it was found that this hadith is of authentic quality, because (1) All narrators are tsiqah. (2) The hadith of the hadith is continued. (3) This hadith does not contain syadz, because there is no contradiction with the naqli propositions, namely the Qur'an and Hadith which have a higher quality sanad. (4) This hadith does not contain 'illat, because there is no contradiction with the aqli argument, namely with common sense, senses and science. Based on simultaneous analysis; This hadith has 4 tabi' hadiths. However, because in terms of the quality of the hadith it already has authentic quality, then the existence of this tabi' hadith has no effect in improving its quality. As for the syawahid, it turns out that 2 martyrdom hadiths were found, this means that the hadith was narrated by two companions, namely Abdurrahman bin Auf and Usamah bin Zaid.